Skeletal stability following mandibular advancement with and without advancement genioplasty - Van der Linden, Carina (My University, 2013)
The correction of most skeletal class II mandibular deficient cases require the surgical advancement of the mandible for the treatment of the malocclusion. Often genioplasty is included to the procedure to improve the soft tissue profile.2,30 Long term skeletal stability is an important goal for the surgeon and orthodontist following Bilateral Sagittal Split Osteotomy (BSSO) and is influenced by the muscles attached to the mandible. Following the surgical advancement of the mandible the suprahyoid muscle complex is certainly stretched and even more so when the procedure is combined with surgical advancement of the chin.10,11 This retrospective comparative study determined the long term skeletal stability of 29 patients, whom had undergone surgical advancement of the mandible by means of BSSO with advancement genioplasty, compared to 29 patients whom had undergone mandibular advancement surgery (BSSO) without advancement genioplasty. All the subjects were evaluated using pre-operative (T1), 1 week post-operative (T2) and at least 6 months (T3) follow-up cephalometric radiographs. This research report concluded that the post-operative hard tissue relapse following BSSO advancement, with or without genioplasty, was clinically insignificant.
Submitted in partial fulfillment of the requirements for the degree of Master in the Science of Dentistry, in the department of Oral and Maxillofacial Surgery, at the University of the Witwatersrand, Johannesburg.
Keywords: Mandible--surgery